2022
DOI: 10.1021/acsaelm.1c01070
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance MoS2 Complementary Inverter Prepared by Oxygen Plasma Doping

Abstract: Two-dimensional transition-metal chalcogenide has become one of the most promising materials for miniaturization beyond Moore’s law due to its atomic-level thickness and excellent semiconductor properties. The inverter is the most basic logic gate circuit. Using double-temperature zone chemical vapor deposition and oxygen plasma doping technique, we obtained n-type and p-type MoS2 materials and designed an MoS2 CMOS inverter, showing excellent electrical performance. Under the condition of V dd = 5 V, the peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 45 publications
(48 reference statements)
1
13
0
Order By: Relevance
“…A fluorine peak was not observed in the measurement. The oxygen incorporation suggests the formation of MoO 3 on the backchannel surface that results in a negatively charged defect, consistent with previous reports on the p-type doping in exfoliated or CVD MoS 2 with oxygen. By reducing t s to less than 15 nm, the oxygen-doped layer and the accumulation region become closer, leading to a positive shift in the threshold voltage (Figure (b,c)). The oxygen doping concentration in the channel layer is estimated to be ∼1 × 10 19 cm –3 , extracted from the V th variation for t s < 15 nm (eq ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…A fluorine peak was not observed in the measurement. The oxygen incorporation suggests the formation of MoO 3 on the backchannel surface that results in a negatively charged defect, consistent with previous reports on the p-type doping in exfoliated or CVD MoS 2 with oxygen. By reducing t s to less than 15 nm, the oxygen-doped layer and the accumulation region become closer, leading to a positive shift in the threshold voltage (Figure (b,c)). The oxygen doping concentration in the channel layer is estimated to be ∼1 × 10 19 cm –3 , extracted from the V th variation for t s < 15 nm (eq ).…”
Section: Resultssupporting
confidence: 89%
“…The oxygen doping concentration in the channel layer is estimated to be ∼1 × 10 19 cm −3 , extracted from the V th variation for t s < 15 nm (eq 1). 44 Electrical stability measurements of the TFT structures correlate with the measured device characteristics. It was found that reducing the MoS 2 bulk thickness from 65 to 15 nm improved the electrical stability by ∼6% of the TFTs operating under constant dc bias (Figure S7).…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…Oxygen molecules capture electrons in MoS 2 (ref. [66][67][68] and at the dangling bonds of the 2D material defect sites the chemical and physical adsorption of molecules can be enhanced. [69][70][71] Although the amount of adsorbed molecules should be reduced under vacuum conditions, ion irradiation can lead to the formation of chemically adsorbed MoO 3 at the defect edges, which would be very resistant to vacuum assisted desorption 33 and could also explain the observed reduction in ndoping.…”
Section: Resultsmentioning
confidence: 99%
“…Since the discovery of graphene, bidimensional (2D) materials stood out as materials presenting outstanding properties to be explored in a myriad of applications. Photovoltaic devices, , hydrogen evolution reaction (HER) catalyst, photodetectors, DNA sensors, transistors, and Li-ion batteries , are examples of technologies that could profit from such properties. Transition metal dichalcogenides (TMDs) are a class of these materials with a lamellar structure similar to that of graphite.…”
Section: Introductionmentioning
confidence: 99%